Evaluation of the causal effects of immune cells on ischemic stroke: a Mendelian randomization study - Wang, Kunyu; Zhang, Beilin; Li, Min; Duan, Hanying; Jiang, Zhuoya; Gao, Su; Chen, Jing; Fang, Shaokuan (Frontiers in Immunology, 2024)
Background Ischemic stroke (IS) is a cerebrovascular disease caused by various factors, and its etiology remains inadequately understood. The role of immune system dysfunction in IS has been increasingly recognized. Our objective was to evaluate whether circulating immune cells causally impact IS risk. Methods We conducted two-sample Mendelian randomization analyses to evaluate the causal effects of 731 immune cell traits on IS, utilizing publicly available genome-wide association studies (GWAS) summary statistics for 731 immune cell traits as exposure data, and two GWAS statistics for IS as outcome data. A set of sensitivity analyses, including Cochran’s Q test, I2 statistics, MR-Egger intercept test, MR-PRESSO global test, and leave-one-out sensitivity analyses, were performed to assess the robustness of the results. Additionally, meta-analyses were conducted to combine the results from the two different IS datasets. Finally, we extracted instrumental variables of immune cell traits with causal effects on IS in both IS datasets for SNP annotation. Results A total of 41 and 35 immune cell traits were identified to have significant causal effects on IS based on two different IS datasets, respectively. Among them, the immune cell trait CD62L- plasmacytoid Dendritic Cell AC and CD4+ CD8dim T cell%leukocyte respectively served as risk factor and protective element in both IS datasets. The robustness of the causal effects was confirmed through the sensitivity analyses. The results of the meta-analyses further support the causal effects of CD62L- plasmacytoid Dendritic Cell AC (pooled OR=1.030, 95%CI: 1.011–1.049, P=0.002) and CD4+ CD8dim T cell%leukocyte (pooled OR=0.959, 95%CI: 0.935–0.984, P=0.001). Based on these two immune cell traits, 33 genes that may be related to the causal effects were mapped. Conclusions Our study demonstrated the potential causal effects of circulating immune cells on IS, providing valuable insights for future studies aimed at preventing IS.